Annealing temperature modify of crystalline structure, magnetic properties and antibacterial performance in nickel substituted cobalt ferrite nanoparticles utilizing natural-fine-sediment - Bestari, Laksmita Farah; Iqlimatussholihah, Lathifah; Prasetya, Nurdiyantoro Putra; Kusumandari; Utari; Riyatun; Purnama, Budi (Communications in Science and Technology, 2024)
This study details the nickel-substituted cobalt ferrite nanoparticle employing natural fine sediment (NiCFO-fs) annealing temperature dependency of crystalline and magnetic characteristics. The NiCFO-fs nanoparticles were prepared by the coprecipitation method with varying annealing temperatures (200-500°C with increment of 100°C for five hours). As a comparison, Ni-CFO was also synthesized using pure analytical chemicals (NiCFO-pa). The XRD results showed that the whole Ni-CFO nanoparticles established an inverse spinel face center cubic (fcc) order according to space group Fd-3m for both NiCFO-fs and NiCFO-pa. There was no additional peak, indicating that Ni2+ cations successfully substituted in cobalt ferrite nanoparticles. In case of NiCFO-fs nanoparticle samples, a crystallite size (D) decreased with the increasing annealing temperature (Ta), namely 45.72 nm, 37.35 nm, 25.95 nm, and 20.51 nm. In contrast to NiCFO-pa, the D increased with the increase of the Ta, i.e., 19.67 nm, 20.74 nm, 21.99 nm, and 23.33 nm. Meanwhile, FTIR results showed the presence of metal-oxygen bonds at 551-586 cm-1 and 384-391 cm-1 at tetrahedral (k1) and the octahedral (k2) sites for both NiCFO-fs and NiCFO-pa nanoparticles samples. The VSM result showed that a narrow hysteresis curve was observed for the NiCFO-fs sample compared to NiCFO-pa. The NiCFO-fs nanoparticles owing the smallest coercive field (HC) of 79.5 Oe were attained for the Ta of 300°C. In case of NiCFO-fs samples, magnetization saturation (MS) decreased with the increase of the Ta in contrast to NiCFO-pa samples. Here, the redistribution of two and three plus ions in the sub-lattice k1 and k2 locations should be encouraged by the Jahn-Teller phenomenon through strain-induced magnetism. The findings of the antibacterial test indicated that the potential of NiCFO based on natural materials (fine sediment) was higher than that of NiCFO based on pure analytical chemicals. This result was also supported by the emergence of ZOI magnitudes for all NiCFO-fs materials compared to NiCFO-pa that was only at Ta = 300°C.